The influence of nozzle chamber structure and partial-arc admission on the erosion characteristics of solid particles in the control stage of a supercritical steam turbine. (15th March 2015) - Cai, Liu-xi; Wang, Shun-sen; Mao, Jing-ru; Di, Juan; Feng, Zhen-ping
Abstract: Reducing solid particle erosion of blades is one of the most urgent problems for supercritical steam turbine power generation technology. Based on the erosion rate models and the particle rebound models of blade materials obtained through accelerated erosion test under high temperature, systematic numerical simulations of the complex steam-particle flow in high pressure inlet flow channel and governing stage cascade of a supercritical steam turbine with four control valves was performed in this paper. The influence the typical nozzle chamber structure and partial-arc admission on the erosion characteristics of control stage blades was first investigated. Results show that erosion condition of nozzles in the same nozzle segment vary greatly along circumferential direction, while erosion damage to the leading edge of different circumferential rotating blades is uniform. Compared with four-valve opening condition, erosion weight-loss of the whole nozzle segment increases by 14% and 25% under three-valve opening condition and two-valve opening condition, respectively. Besides, under the partial-arc admission conditions, some large particles coming from the steam admission nozzle segment will collide back and forth between vanes and rotating blades in the downstream nozzle segment without steam admission, thus causing certain erosion to the trailing edge of nozzle suction side. Highlights: Erosion model and particle rebound model are established based on test results. Oxide scales are prone to concentrate in the nozzle channel near horizontal split. Erosion is uneven to nozzles but uniform to rotors along circumferential direction. Erosion of cascade deteriorates rapidly under partial-arc admission conditions. Nozzle segment without steam intake will be eroded by particles under partial load.